Comparative Studies on Strategies for Combating Corruption between Nigeria and Iraq (Journal of Governance and Development (JGD), 2023)
Corruption is the great ailment that disturbed most of the nation statesacross the globe, its predicament is worst in the developing states thandeveloped one. The sinister of corrupt practices have attracted the attentionof international community to designed some strategies for combating itsmenace, this has adversely makes the member states to masterminds theirstrategies or review the existent one for enhancing probity, accountabilityand national development. This study compares the strategies for combatingcorruption between Nigeria and Iraq. The study employed qualitativetechniques through interview method in obtaining data from the stakeholders,academics and politicians. The study revealed that both Nigeria and Iraqhave institutional strategies for fighting against grafts in their country. Itwas also revealed that the strategies are effective in Nigeria while theyare ineffective in Iraq; it also pointed that all strategies were facing somechallenges such as autonomy, political interference, and funding, inadequatestaff among others. The paper recommends that the anti-grafts institutionsshould be strengthen, holistic approach, and enhancing political will towardsdiscarding the above challenges facing the institutions. The role of the mediaand civil society should also be recognized in fighting against corruption intheir respective states.